The Influence of Location and Price on Traders' Decision Making in Renting a Kiosk at Ya'ahowu Market, Gunungsitoli City - Iwarman Waruwu; Otanius Laia; Yupiter Mendrofa; Eduar Baene (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the influence of location and price on traders' decision making in renting kiosks in the Ya'ahowu market in Gunungsitoli city. The main objective of this study is to determine whether there is a significant influence of promotion on decision making, the influence of price on decision making, and the simultaneous influence of location and price on traders' decision making. Based on the results of the determination coefficient test, the R Square value of 0.718 or 71.8% indicates that the Location variable (X1) has a strong influence on decision making (Y). In addition, the Adjusted R Square value of 0.674 indicates that the Location and Price variables (X2) together influence decision making by 67.4%. The results of the F test with a significance value of 0.000 <0.05 and a calculated F value of 80.047>244, indicate that H3 is accepted, which means that there is a significant influence of location and price variables on decision making.